Reference gene selection and evaluation for expression analysis using qRT-PCR in Galeruca daurica (Joannis). Issue 3 (7th November 2016) - Tan, Y.; Zhou, X.-R.; Pang, B.-P.
Abstract: Quantitative real-time PCR (qRT-PCR) has been used extensively to analyze gene expression and decipher gene function. To obtain the optimal and stable normalization factors for qRT-PCR, selection and validation of reference genes should be conducted in diverse conditions. In insects, more and more studies confirmed the necessity and importance of reference gene selection. In this study, eight traditionally used reference genes in Galeruca daurica (Joannis) were assessed, using qRT-PCR, for suitability as normalization genes under different experimental conditions using four statistical programs: geNorm, Normfinder, BestKeeper and the comparative Δ C t method. The genes were ranked from the most stable to the least stable using RefFinder. The optimal suite of recommended reference genes was as follows: succinate dehydrogenase ( SDHA ) and tubulin-alpha ( TUB-α ) for temperature-treated larvae; ribosomal protein L32, SDHA and glutathione S-transferase were best for all developmental stages; ACT and TUB-α for male and female adults; SDHA and TUB-α were relatively stable and expressed in different tissues, both diapause and non-diapause adults. Reference gene evaluation was validated using expression of two target genes: the P450 CYP6 gene and the heat shock protein gene Hsp70 . These results confirm the importance of custom reference gene selection when studies are conducted under diverse experimental conditions. A standardized qRT-PCR analysis procedure for gene functional studies is provided that could be useful in studies on other insect species.